2000
DOI: 10.1111/j.1439-0450.2000.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long‐term Oral Administration of an Immunostimulant Diet on Innate Immunity in Sea Bass (Dicentrarchus labrax)

Abstract: Immunostimulants represent a modern and promising tool in aquaculture, enhancing the resistance of cultured fish to disease and stress. This study investigated the effect of a combination of dietary glucans, a-tocopherol and ascorbic acid on the innate immune response of cultured sea bass (Dicentrarchus labrax). After 5 weeks of adaptation on a commercial diet containing 100 p.p.m. ascorbic acid and 200 p.p.m. atocopherol, sea bass were switched to a diet supplemented with 2 % b-1.3/b-1.6 glucans and ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…(Valente et al 2006) and in European seabass fed diets with algal extract (Lauridsen and Buchmann 2010). On the other hand, an increase in lysozyme concentration was reported in European seabass when fed a seaweed supplemented diet (Peixoto et al 2016c) and when fed a combination of dietary glucans and vitamins (Bagni et al 2000), contradicting present results. Given this, we hypothesize that the beneficial effects of seaweeds on the innate immune response may be highly influenced by biotic and abiotic factors such as species, age, weight, rearing water conditions, and/or seaweed composition.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…(Valente et al 2006) and in European seabass fed diets with algal extract (Lauridsen and Buchmann 2010). On the other hand, an increase in lysozyme concentration was reported in European seabass when fed a seaweed supplemented diet (Peixoto et al 2016c) and when fed a combination of dietary glucans and vitamins (Bagni et al 2000), contradicting present results. Given this, we hypothesize that the beneficial effects of seaweeds on the innate immune response may be highly influenced by biotic and abiotic factors such as species, age, weight, rearing water conditions, and/or seaweed composition.…”
Section: Discussioncontrasting
confidence: 98%
“…To solve this, alternative strategies of environmental-friendly techniques are constantly being explored. These alternatives include chemical therapy, vaccination (Bagni et al 2000;Sakai 1999), or the application of dietary immunostimulants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17]. 50 ml of serum was added as triplicate into the plate and then mixed with 50 ml of PBS (pH 5.8).…”
Section: Lysozyme Activitymentioning
confidence: 99%
“…In fact, in vitro studies have demonstrated that macrophages elicit a respiratory burst following beta-glucan exposure but also that the response of isolated cells is immediate and fades after prolonged stimulation (Chettri et al 2010). However, feeding sea bass with glucan-supplemented feed (0.1%) for extended periods did not result in decreased responsiveness of fish (Bagni et al 2000(Bagni et al , 2005. Neither did long term administration of low dosages (0.01%-0.05%) to rohu carp (Labeo rohita) lead to a decrease of the resistance to challenge infections using Aeromonas hydrophila and Edwarsiella tarda (see Misra et al 2006).…”
Section: Introductionmentioning
confidence: 99%